Helmet Sales Information System Web based on Studio Shop Jakarta Custom Helmet - Basyiri, Hilman (Institute of Computer Science (IOCS), 2025)
Systems information of helmet sales based on the web at Studi Helm Custom Store. The purpose of this study was to analyze and design of web-based sales system in Stores Studio Helm Custom. It is made to increase profits and make it easy for customers to order and buy helmets. This method uses data collection, analysis (surveys, interviews, and literature) and design (form inputs, processes, reports, and database). The results of this study are web-based sales system that can be used by customers 24 hours. The conclusion is a web-based sales system has facilities such as information pages, the page order, and cancel the page.